1993
DOI: 10.1002/ijc.2910540303
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody detects heterogeneity in vascular endothelium of tumours and normal tissues

Abstract: A new murine monoclonal antibody (MAb), E-9, has been raised using tissue-cultured human umbilical vein endothelial cells. The antigen recognized by this MAb is a peptide of 170 kDa under non-reducing conditions and 96 kDa under reducing conditions. MAb E-9 showed marked heterogeneity in its distribution in various tissues. The antigen recognized by it was present in vascular endothelial cells of all tumours, foetal organs and in regenerating and inflamed tissues. It stained a few normal tissues. However, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
103
2
3

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(109 citation statements)
references
References 19 publications
1
103
2
3
Order By: Relevance
“…These data are not in agreement with previous reports obtained with other endoglin-specific antibodies 19,20 in which several normal adult tissues were negative for this antigen. These discrepancies could be due to several reasons: the immunohistochemistry conditions used could have entailed a different sensitivity of the staining, or the antibody itself could have a different affinity for the antigen; the MAb could react with a different isoform, even though only 2 isoforms have thus far been described with a sequence difference in the intracytoplasmic tail; it could recognize an epitope that is more exposed than other epitopes on the endothelial cell surface.…”
Section: Analysis Of Endoglin Expression In Neoplastic and Normal Humcontrasting
confidence: 99%
See 3 more Smart Citations
“…These data are not in agreement with previous reports obtained with other endoglin-specific antibodies 19,20 in which several normal adult tissues were negative for this antigen. These discrepancies could be due to several reasons: the immunohistochemistry conditions used could have entailed a different sensitivity of the staining, or the antibody itself could have a different affinity for the antigen; the MAb could react with a different isoform, even though only 2 isoforms have thus far been described with a sequence difference in the intracytoplasmic tail; it could recognize an epitope that is more exposed than other epitopes on the endothelial cell surface.…”
Section: Analysis Of Endoglin Expression In Neoplastic and Normal Humcontrasting
confidence: 99%
“…4) A strong positivity was observed with this MAb, already characterized as specific for human endoglin. 20 The A11 and E9 MAbs were compared as well in immunohistochemistry on human glioblastoma and breast carcinoma samples (not shown), and the same staining pattern was observed.…”
Section: Antigen Purification and Characterizationmentioning
confidence: 75%
See 2 more Smart Citations
“…The association of CD105 with angiogenesis initially came from Wang et al (1993) who found that monoclonal antibodies to CD105 reacted strongly with the endothelium in various tumour tissues but only weakly in normal tissues. CD105 is overexpressed on endothelial cells of tissues undergoing neovascularisation and is strongly expressed in breast cancer (Bodey et al, 1998).…”
mentioning
confidence: 99%